Efektivitas Pemberian Cairan Soil Stabilizer Pada Tanah Wadah Budidaya Udang Vaname (Litopenaeus vanamei) - Nurussalam, Wildan; Nirmala, Kukuh; Aziz, Haikal (Jurnal Akuakultur Sungai dan Danau, 2024)
Leaking ponds based on soil is often a problem in shrimp farming. This can trigger a potential increase in production costs, so that vaname shrimp farmers can experience losses. One solution that can be sought to prevent leakage of ponds based on soil is soil stabilization, namely by adding additives to the soil in the form of soil stabilizer liquid. This study aims to determine the effectiveness of providing soil stabilizer with a chemical base that has polymer ionic bonds in the soil of the vannamei shrimp (Litopeneaus vanamei) culture container. This study used a completely randomized design (CRD) with two treatments, namely control and treatment with the addition of soil stabilizer fluid with the same dose, each with four replications. The research was carried out through four stages, namely the stage of testing soil properties, making soil samples, Unconfined Compressive Strength (UCS) test, and soil permeability. The results of the treatment with soil stabilizer fluid had an effect on the permeability of the sample soil. The control coefficient value is 4.94 x 10-7, while for the sample soil treatment, the average value is 2.62 x 10-7. Based on the results of statistical tests, the results were significantly different from the treatment soil. The pressure strength test after being tested using statistical analysis did not differ between treatments. The addition of soil stabilizer can reduce the value of soil permeability. Provision of soil stabilizer can reduce the value of permeability up to 47%. However, the addition of the soil stabilizer did not produce a significant difference in pressure strength..